Felicity saves the day : a summer story - Tripp, Valerie, 1951- (American girls collection., 1992)
During a visit to her grandfather's plantation in Virginia during the summer of 1775, Felicity's loyalty is torn between her father and Ben, her father's apprentice who needs her help as he runs away to join George Washington's army of Patriots.